2011
DOI: 10.1371/journal.pmed.1001128
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Medical Male Circumcision: Logistics, Commodities, and Waste Management Requirements for Scale-Up of Services

Abstract: Dianna Edgil and colleagues evaluate the supply chain and waste management costs needed to deliver mobile medical male circumcision services to 152,000 men in Swaziland, finding that per-procedure costs almost double when these factors are taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 5 publications
1
34
0
Order By: Relevance
“…The cost per person tested ranged from US$2.45 to US$881.63 using different community-based testing approaches (Table 6) [29],[45],[71],[74],[107],[117],[122],[131][136]. The cost per person tested was US$2.45 to US$14.37 for door-to-door testing, US$3.26 to US$33.54 for mobile testing, US$12.91 for hospital testing, US$15.30 to US$203.04 for index testing, US$21.28 to US$29.56 for testing at a fixed HTC site, US$126.48 for church-based testing, US$92.83 to US$881.63 for community-based testing for key populations, and US$93.73 for testing at an HIV clinic.…”
Section: Resultsmentioning
confidence: 99%
“…The cost per person tested ranged from US$2.45 to US$881.63 using different community-based testing approaches (Table 6) [29],[45],[71],[74],[107],[117],[122],[131][136]. The cost per person tested was US$2.45 to US$14.37 for door-to-door testing, US$3.26 to US$33.54 for mobile testing, US$12.91 for hospital testing, US$15.30 to US$203.04 for index testing, US$21.28 to US$29.56 for testing at a fixed HTC site, US$126.48 for church-based testing, US$92.83 to US$881.63 for community-based testing for key populations, and US$93.73 for testing at an HIV clinic.…”
Section: Resultsmentioning
confidence: 99%
“…Although we assumed that only one size of the device would be required, there are five different adult PrePex ring sizes. Logistical management systems necessary to deliver and maintain more than one device size to various facilities would likely add to the PMC cost [34]. Finally, a recent study found healing time under PMC was approximately two weeks longer than under a standard surgical method [25] which could potentially lead to increased post-procedure visits and a longer recommended abstinence period.…”
Section: Discussionmentioning
confidence: 99%
“…Costing data were obtained from a single region in Kenya and costs may be different in other regions in the country or in other nations. We did not include supply chain management costs or waste disposal costs, which have been found to add substantially to the per-MC cost [34]. The calculations of the PrePex costs were largely hypothetical, but based on information available from published studies and from observed program costs, many of which would be fixed regardless of MC method.…”
Section: Discussionmentioning
confidence: 99%
“…Edgil et al [29] describe a costing framework for these program components for Swaziland, emphasising the advantages of a standard kit of the consumables and dedicated instruments necessary for one male circumcision procedure [30],[31].…”
Section: Determining Costs Of Scale-upmentioning
confidence: 99%